The Correlation Between Students Vocabulary and Speaking Ability at Seventh Grade in SMPN 2 Dua Koto Kabupaten Pasaman - Seprisa, Seprisa; Dewi, Merry Prima; Reflinda, Reflinda; Safitri, Widya (Journal of Educational Management and Strategy, 2022)
This research was motivated by several problems of class VII students of SMPN 2 Dua Koto, Pasaman Regency related to learning English such as vocabulary and speaking. One of them is that some students have low scores in the vocabulary test and speaking test, the students' low ability to speak English, they do not have enough vocabulary. Therefore, this study was conducted so that the researchers found out whether there was a relationship between the students' vocabulary and the speaking achievement of the fifth grade students of SMPN 2 Dua Koto. This study uses a quantitative approach to the type of correlation design. The population in this study were all class VII at SMPN 2 Dua Koto consisting of 3 classes with a sample consisting of 72 students taken through total sampling technique. Data was collected through a vocabulary test and speaking test. The results showed that there was a relationship between vocabulary and speaking ability of seventh grade students of SMPN 2 Dua Koto for the academic year 2020/2021. Based on the results of this study, it can be concluded that vocabulary has a positive important role for speaking ability. That is, if students have a large vocabulary, then they will have good speaking skills. on the other hand, if students have low vocabulary, they have low speaking ability. So, this study was conducted to find the relationship between vocabulary and speaking ability of students in the seventh grade of SMPN 2 Dua Koto, Pasaman Regency. Abstrak Penelitian ini dilatarbelakangi oleh beberapa masalah siswa kelas VII SMPN 2 Dua Koto Kabupaten Pasaman terkait dengan pembelajaran bahasa Inggris seperti vocabulary dan speaking. Diantaranya siswa memiliki nilai yang rendah dalam tes kosa kata dan tes berbicara, rendahnya kemampuan siswa dalam berbicara bahasa Inggris, mereka tidak memiliki kosakata yang cukup. Oleh karena itu, penelitian ini dilakukan agar peneliti mengetahui apakah ada hubungan antara kosa kata siswa dengan pencapaian berbicara siswa kelas Vll SMPN 2 Dua Koto. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis design korelasi. Populasi dalam penelitian ini adalah seluruh kelas Vll di SMPN 2 Dua Koto terdiri 3 kelas dengan sampel yang terdiri 72 siswa yang diambil melalui teknik total sampling. Pengumpulan data dilakukan melalui test kosa kata dan test berbicara. Hasil penelitian menunjukkan bahwa ada hubungan antara kosakata dan kemampuan berbicara siswa kelas VII SMPN 2 Dua Koto tahun ajaran 2020/2021. Berdasarkan hasil penelitian ini, dapat disimpulkan bahwa kosakata memiliki peran penting yang positif bagi kemampuan berbicara. Artinya, jika siswa memiliki kosakata yang banyak, maka mereka akan memiliki kemampuan berbicara yang baik. sebaliknya, jika siswa memiliki kosa kata yang rendah, mereka memiliki kemampuan berbicara yang rendah. Jadi, penelitian ini dilakukan untuk menemukan hubungan antara kosakata dan kemampuan berbicara siswa di kelas tujuh SMPN 2 Dua Koto, Kabupaten Pasaman.